FACTORS AFFECTING THE EDUCATION AND REPAYMENT OF RECEIVABLES - N. Spiridonova; N. Rozhkova (Вестник университета)
The article is devoted to the issues related to the accounts receivable of the organization, which for the debtor is a source of free funds, and for the creditor is the possibility of increasing the range of distribution of its products, services, and expansion of the sales market. Based on a theoretical review of existing studies, the article presents internal and external factors affecting the value of receivables. Actions are considered and discussed, including the most common of them, affecting the formation of receivables and its repayment